Stem cell therapy applied for digestive anastomosis: Current state and future perspectives - Trébol López, Jacobo; Georgiev Hristov, Tihomir; Pascual Miguelañez, Isabel; Guadalajara Labajo, Hector; García Arranz, Mariano; García Olmo, Damián (My University, 2022)
Digestive tract resections are usually followed by an anastomosis. Anastomotic leakage, normally due to failed healing, is the most feared complication in digestive surgery because it is associated with high morbidity and mortality. Despite technical and technological advances and focused research, its rates have remained almost unchanged the last decades. In the last two decades, stem cells (SCs) have been shown to enhance healing in animal and human studies; hence, SCs have emerged since 2008 as an alternative to improve anastomoses outcomes.